Persepsi Dukungan Organisasi dan Komitmen Afektif Organisasi: Peran Mediasi Keterikatan Karyawan pada Karyawan Pertelevisian - Nina Febriani Panuju; Wustari L. Mangundjaya (Psikohumaniora: Jurnal Penelitian Psikologi, 2018)
Television broadcasting company has unique working condition with various challenges and demands to keep making innovations. This research aimed to study working conditions in television broadcasting companies in Indonesia using three variables, namely affective organization commitment (AOC), employee engagement (EE), and perceived organizational support (POS). The data were obtained by using 3 measurements, i.e. Affective Organization Commitment scale, Survey of perceived organizational support (SPOS), and Aon Hewitt Employee Engagement (AHEE). The respondents consisted of 139 employees of Indonesian television broadcasting companies which were obtained from convenience sampling with the criteria of being a permanent employee, having worked at least a year, and being 23-55 years old. Statistical techniques PROCESS that was developed by Hayes were applied to test the mediation role. The result showed that all variables were positively related and EE acted as partial mediator to correlation between POS and AOC,